A Randomized Prospective Pilot Study Investigating the Feasibility and Effects of High Intensity Laser Therapy for Women with Vulvodynia. (1st August 2022) - Morin, M; Paré, J; Dumont, V; Bérubé-Lauzière, Y; Tu, LM
ABSTRACT: Introduction: Laser therapy and more specifically, High Intensity Laser Therapy (HILT), is an emerging non-invasive and non-ablative treatment modality, that appears promising for treating provoked vestibulodynia (PVD). However, evidence supporting this treatment remains limited so far as no prospective study has examined the feasibility, acceptability and effects in women with PVD. Objective: 1) to evaluate the feasibility and acceptability of HILT in women with PVD and 2) to explore the effects of active and sham HILT on pain intensity during intercourse. Methods: Women aged 18-45 years suffering from PVD participated in this randomized pilot study. Women were included if they reported pain at the entry of the vagina during vaginal intercourse (intensity of ≥5 on a numerical rating scale (NRS)) for more than three months. A standardized pelvic examination was performed by a gynecologist from our team to confirm the eligibility of participants. Women were randomized to receive bi-weekly sessions of active (n=20) or sham HILT (n=20) for 6 weeks. Women were assessed at baseline and post-treatment (2 weeks after the end of the treatment). Patients, outcome assessors and data analysts were blinded to group assignation. The attendance rate at laser sessions (≥80% of participants attending ≥10 sessions), the dropout rate (˂15%) and the absence of serious adverse events served as feasibility and acceptability outcomes and benchmarks. Patients' perceived improvement and satisfaction were also assessed. The effects of treatment on mean pain intensity during intercourse were measured. Results: A total of 45 women were screened by the gynecologist and 40 were enrolled in the study (n=5 were excluded because of other diagnoses i.e. infection, dermatological conditions). Among the women included, only one participant in the real HILT group dropped out of the study at post-treatment due to time constraints. Regarding the attendance rate for treatment, the 12 sessions were completed by all participants, except for two women who had 11 sessions due to Covid-related reasons. No serious side effects were observed in either group. In regard to patients' global impression of change, 79% of women reported significant improvement in the active HILT group as opposed to 47% in the sham group. In the sham group only, 10% reported worsening of their condition. Regarding satisfaction to treatment, women in the active group were more satisfied with a mean of 6.6/10 (SD 2.8) compared to 4.6/10 (SD 3.1) in the sham group (p<0.05). A significant reduction in pain from baseline to post-treatment was found for women in the active HILT group (baseline 7.3±1.3; post-treatment 4.1±2.2; p˂.001) and sham HILT group (baseline 7.4±1.6; post-treatment 5.4±3.2; p=.002). Conclusions: HILT is a feasible and acceptable intervention to treat women with PVD. With the significant improvements observed, findings support conducting a randomized controlled trial to confirm the efficacy of this promising intervention. Disclosure: No